Adjunctive use of VTAMA (tapinarof) 1% cream in the management of new-onset scalp psoriasis in a patient with fistulizing Crohn’s disease on infliximab - Machynia, Kyle T. (International Journal of Research in Dermatology, 2025)
Psoriasis (PsO) frequently coexists with inflammatory bowel disease (IBD), including Crohn’s disease (CD). Patients with CD on tumor necrosis factor (TNF)-alpha inhibitors, such as infliximab (IFX), are at an increased risk for developing PsO. The paradoxical development of PsO in this patient population presents a therapeutic challenge, particularly in those with fistulizing CD, as switching to IL-23 inhibitors is not a viable option due to their reduced efficacy in promoting fistula healing. Effective treatment strategies that can manage PsO without compromising CD control are therefore necessary. Here we report a case of new onset scalp PsO treated with tapinarof 1% cream with significant improvement noted after 2 weeks of application and maintains clearance of scalp PsO with biweekly application.